2011
DOI: 10.1166/jnn.2011.3862
|View full text |Cite
|
Sign up to set email alerts
|

The Role of NADPH Oxidase in Multi-Walled Carbon Nanotubes-Induced Oxidative Stress and Cytotoxicity in Human Macrophages

Abstract: Recent studies suggest reactive oxygen species (ROS) induced in mammalian cells exposed to multi-walled carbon nanotubes (MWCNTs) could mediate the cytotoxicity. This study was conducted to determine the mechanisms responsible for MWCNTs-induced ROS production in human primary macrophages. Our results showed that superoxide levels were significantly increased in a time-dependent manner in blood monocyte-derived macrophages treated with 100 microg/ml MWCNTs for 12 h. Concomitantly, MWCNTs induced membrane trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 0 publications
4
15
0
Order By: Relevance
“…It has been previously reported that genotoxicity effects can result from the direct interaction of nanoparticles with genetic material or secondary damage resulting from particle-induced reactive oxygen species production (Kisin et al, 2011). According to the recent in vitro studies, SWCNTs and MWCNTs induce ROS production in mammalian cells (Sharma et al, 2007;Shvedova et al, 2003;Ye et al, 2009Ye et al, , 2011. In a previous in vivo 5-day inhalation study by the current authors, a 2.57 mm average tube length induced an increased concentration of intracellular H 2 O 2 with a similar trend of DNA damage (Kim et al, 2012b).…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously reported that genotoxicity effects can result from the direct interaction of nanoparticles with genetic material or secondary damage resulting from particle-induced reactive oxygen species production (Kisin et al, 2011). According to the recent in vitro studies, SWCNTs and MWCNTs induce ROS production in mammalian cells (Sharma et al, 2007;Shvedova et al, 2003;Ye et al, 2009Ye et al, , 2011. In a previous in vivo 5-day inhalation study by the current authors, a 2.57 mm average tube length induced an increased concentration of intracellular H 2 O 2 with a similar trend of DNA damage (Kim et al, 2012b).…”
Section: Discussionmentioning
confidence: 99%
“…Because metal catalysts are not used in the production of CNHs, this possibility can be excluded. Ye et al (2011) found that MWNT could activate the NADPH oxidase in human macrophages, which may contribute to ROS generation. Sharma et al (2007) concluded that the mitochondria is not involved in SWNT induced ROS production and that SWNT induces oxidative stress by loss of antioxidants, but how does SWNT affect the antioxidants was still unclear.…”
Section: Mechanism Of Ros Generation Induced By Cnh Laoxmentioning
confidence: 99%
“…Among these studies, most report that oxidative stress and the production of reactive oxygen species (ROS), which are involved in the apoptosis pathway (Cheng et al, 2011), are the major adverse effects mediated by carbon nanotubules (Ravichandran et al, 2009;Srivastava et al, 2011;Pacurari et al, 2008;Lacotte et al, 2008;Liu et al, 2013;Yang et al, 2009). Although some previous reports discussed ROS generation by carbon nanotubules (Kagan et al, 2006;Lacotte et al, 2008;Sharma et al, 2007;Pulskamp et al, 2007;Ye et al, 2011), a detailed understanding of the mechanisms and pathways involved is currently lacking.…”
Section: Introductionmentioning
confidence: 99%
“…This might be the reason why other studies in which ROS was measured after more than 4 h exposure to CNT showed inconsistent results [50,117-119]. Several studies [112,120] concluded that cytotoxicity can be attributed to oxidative stress. Interestingly, no cytotoxic effect was found in this study in three different MWCNT-treated cells, although generation of ROS was observed in all cell lines used.…”
Section: Discussionmentioning
confidence: 99%